Students’ Needs Analysis of Business English At ESP Class For Business Administration Department At Nommensen HKBP University - Yensi Nurisa Simaremare; Erika Sinambela; Sondang Manik (Jayapangus Press, 2023)
Nowadays, practically all job profession criteria demand job candidates to be proficient in the language of their preferred professional industry, particularly English. This research was conducted to examine the challenges faced by the Business Administration Department, specifically the second-semester students at Nommensen HKBP University, in using English and their need for Business English in ESP classes. It follows Hutchinson and Waters' theory, which consists of target situation needs and learning needs. Target situation needs include